Comparing the epistemic burdens of liberal transition and central planning - Max Molden (The Review of Austrian Economics, 2024)
Epistemic burdens are ubiquitous. Whenever people act, their success largely depends on their knowledge. While epistemic burdens are widely recognised when it comes to centrally planning the economy, Scott Scheall has drawn attention to the epistemic burdens involved in transitioning to a liberal society. In this regard, Scheall raises the question of whether these epistemic burdens might actually be as high as those faced by central planners. In this paper, I examine the epistemic burdens of liberal transitions and compare them to those of central planning the economy. Also looking at empirical cases, I tentatively conclude that transitioning to a liberal society is epistemically less burdensome, primarily because the liberal society provides a relatively stable objective and because theoretical knowledge about the necessary cultural preconditions and the institutional framework already exists. However, liberal transitions are still epistemically burdensome, especially when it comes to getting to the desired societal framework. Furthermore, when the required cultural preconditions are absent, it may well be that the epistemic burdens are insurmountable.
Keywords: B00; B25; B53; D80; P50; 330; Epistemic burdens; Hayek; Knowledge problem; Liberal transition; Scheall